Harvest bumper potatoes through little tubers - Paul, Vijay; Ezekiel, R. (Indian Horticulture, 2019)
Little potato tubers offer a virus-free, cost-effective and alternative planting material that can effectively bridge the gap between demand and supply of quality propagation material in potato. The little tuber production (which is in accordance with time schedule of potato crop production), there exists a strong possibility of using little tubers as quality planting material in plains and hills. Little tubers (0.3 - 1.0 g or more) can be planted directly in field at a half the normal spacing, i.e. 60 cm Ã— 10 cm with yield performance at par to that of normal seed potato tubers (40 - 60 g, planted at normal spacing of 60 cm Ã— 20 cm). More research is required to fine tune this technology of little tuber production for its large-scale production, thereby using them as planting material.